Perlindungan Hukum Karyawan Terkait Pengurangan Gaji Akibat Pandemi Covid-19 pada Hotel dan Restaurant di Area Seminyak - Anak Agung Arista Purnama Sari; Anak Agung Sagung Laksmi Dewi; I Wayan Arthanaya (Fakultas Hukum Universitas Warmadewa, 2021)
The problem faced by the company during the Covid-19 pandemic was related to the financial crisis, so that paid workers are 20-30% of the initial salary in the work agreement because the Covid-19 pandemic. The formulation of the problem is how to determine the reduction in employee salaries during the Covid19 pandemic and the application of protection for labor rights during the Covid-19 pandemic in hotels and restaurants in the Seminyak area? The research method uses empirical legal methods with a fact approach. The results of the study explain the determination of employee salary reductions during the COVID-19 pandemic at hotels and restaurants is carried out on the basis of reduced company income and the company do not want to close the business. The conclusion is that based on the SE of the Ministry of Manpower Number M/3/HK.04/III/2020 of 2020,for companies that limit their business activities due to government policies, they can make payment of wages in accordance with the agreement between employers and workers/laborers. The suggestion from this research that the management of hotels and restaurants is trying to find other alternatives to increase the salary value of employees.